2021
DOI: 10.1002/cac2.12194
|View full text |Cite
|
Sign up to set email alerts
|

The role of non‐coding RNAs in drug resistance of oral squamous cell carcinoma and therapeutic potential

Abstract: Oral squamous cell carcinoma (OSCC), the eighth most prevalent cancer in the world, arises from the interaction of multiple factors including tobacco, alcohol consumption, and betel quid. Chemotherapeutic agents such as cisplatin, 5‐fluorouracil, and paclitaxel have now become the first‐line options for OSCC patients. Nevertheless, most OSCC patients eventually acquire drug resistance, leading to poor prognosis. With the discovery and identification of non‐coding RNAs (ncRNAs), the functions of dysregulated nc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 189 publications
(184 reference statements)
0
37
0
Order By: Relevance
“…Oral squamous cell carcinoma (OSCC) is the eighth most prevalent cancer in the world [ 16 ]. Heterogeneous tumors account for approximately 40% of head and neck squamous cell carcinomas (HNSCCs), including the tongue, upper and lower gums, oral base, and maxillary and buccal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral squamous cell carcinoma (OSCC) is the eighth most prevalent cancer in the world [ 16 ]. Heterogeneous tumors account for approximately 40% of head and neck squamous cell carcinomas (HNSCCs), including the tongue, upper and lower gums, oral base, and maxillary and buccal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous tumors account for approximately 40% of head and neck squamous cell carcinomas (HNSCCs), including the tongue, upper and lower gums, oral base, and maxillary and buccal mucosa. OSCC is caused by the interaction of multiple factors, including tobacco, alcohol, and betel nut [ 16 ]. Since the early diagnosis rate is low, most patients are diagnosed in the late stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSCC refers to a group of heterogeneous tumors originating from the mucosal lining ( Meng et al, 2021 ). Most of these tumors are associated with lifestyle factors, such as smoking, excessive drinking, and betel nut chewing ( Adil et al, 2021 ; Weiße et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, cisplatin-resistance is a headache in chemotherapy, resulting in tumor relapse and poor prognosis [ 53 ]. Emerging evidence showed that lncRNAs may function as vital regulators of chemoresistance in OSCC [ 17 , 106 ]. For instance, the upregulation of HOXA11-AS significantly increased resistance to cisplatin and tumor cell growth, and the knockdown of HOMA11-AS markedly enhanced CDDP-mediated tumor inhibition in vivo [ 53 ].…”
Section: Roles Of Lncrna In Osccmentioning
confidence: 99%